Seismic qualification of crossover piping systems on a sodium-cooled fast reactor with a seismic isolation system - Tomoyoshi WATAKABE; Takahiro OKUDA; Satoshi OKAJIMA (Mechanical Engineering Journal, 2024)
A three-dimensional seismic isolation system has been developed for the conceptual design of a sodium-cooled fast reactor (SFR) in Japan. Between the reactor building equipped with the isolation system and the turbine building with no isolation system, there are main steam crossover piping systems, in which a large displacement would occur, and this is a challenge for developing an SFR with the isolation system. Existing studies of the seismic design of crossover piping were performed on the piping, considering the conditions of light water reactors (LWRs). However, because the SFR operates at elevated temperatures compared with LWRs, the design of crossover piping systems must comply with the design code for elevated temperature components. It must be also considered that the advanced material, Mod.9Cr-1Mo steel, is employed as a material of the crossover piping in the SFR. In this study, we performed seismic evaluation using an example of a crossover piping layout to refer to existing codes on piping. The evaluation results and insight obtained from existing dynamic failure tests of piping components show the knowledge on seismic evaluation of the crossover piping systems in the SFR with the three-dimensional isolation system to achieve the SFR with the three-dimensional isolation system.